2005
DOI: 10.1002/pon.1014
|View full text |Cite
|
Sign up to set email alerts
|

Care and support needs of children and young people with cancer and their parents

Abstract: The importance of psychosocial support services for children with cancer and their families is recognised but evaluation of such services is less well developed with little information available about different patterns of provision. This paper provides an overview of psychosocial support children and their families in the UK receive during and after treatment. It reports the results of a postal survey of 303 families, within which parents and children identified their satisfaction with support services and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
104
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 23 publications
13
104
0
7
Order By: Relevance
“…The results of recent studies have shown that a statistically significant difference was not found between the child self reports and parental proxy reports and the assessments of both groups agreed well with each other in clinical studies on the quality of life of children with chronic diseases (20,36,37). Reading (35) tested PedQL 4.0 Generic Core scale for its reliability and validity and found that the parent forms of the scale were quite applicable, valid and reliable with children aged between 2-16 years old.…”
Section: Discussionsupporting
confidence: 66%
“…The results of recent studies have shown that a statistically significant difference was not found between the child self reports and parental proxy reports and the assessments of both groups agreed well with each other in clinical studies on the quality of life of children with chronic diseases (20,36,37). Reading (35) tested PedQL 4.0 Generic Core scale for its reliability and validity and found that the parent forms of the scale were quite applicable, valid and reliable with children aged between 2-16 years old.…”
Section: Discussionsupporting
confidence: 66%
“…3,4 The 2008 Institute of Medicine report, Cancer Care for the Whole Patient, underscores increased recognition of the importance of identifying unmet psychosocial needs of cancer survivors, 3-6 among whom the overall prevalence of distress is estimated to be as high as 35%. 7 Research has demonstrated high levels of unmet needs in subgroups of survivors, including survivors of breast, 8,9 prostate, 10,11 lung, 12 bowel, 13 childhood/ young adult, 14,15 and skin cancers. 16 In addition to psychosocial needs, survivors report needing support for fatigue, 16 health promotion, 17,18 infertility, 15 economic burdens, obtaining health and/or life insurance, and employment.…”
Section: Introductionmentioning
confidence: 99%
“…1 These young women have unique medical and psychosocial needs, [2][3][4] including concerns about reproductive late effects. [5][6][7][8][9][10] Our limited understanding of how best to address these and other long-term survivorship care needs may be partly related to difficulties recruiting young survivors for research studies. [11][12][13][14] Several factors contribute to recruitment challenges in AYA-aged survivors.…”
mentioning
confidence: 99%